Analysis of the Feasibility of Investing in Taman Melati Dinoyo Apartments, Malang City - Classinta Ard, Bella Astrina; Muhammadun, Haris; Nugroho, Laksono Djoko (Sahabat Publikasi, 2023)
This research aims to investigate the investment potential of Taman Melati Dinoyo Apartments, Malang City as a promising form of property. Through an economic and property market analysis approach, this research explores the factors that influence investment decisions and the impact on local economic growth. An in-depth literature study was used to understand property investment trends and apartment market characteristics. The data analysis method includes collecting primary data through interviews with property developers and other related parties. Additionally, secondary data from financial institutions, local governments and other sources were used to validate the findings. The results of this research identify the main factors that influence apartment investment such as property prices, construction costs, occupancy rates and interest rates. Apart from that, this research can also be a reference for project developers to identify potential risks and stimulate effective mitigation strategies by using investment capital that is used in a ratio of 30% own capital and 70% loans.The analytical method used to analyze this research is data collection, data processing, income analysis, cash flow and reviewing financial aspects using the NPV, IRR, BCR, Payback Period method. The final stage of work is analyzing the sensitivity of investment costs to investment costs, Sensitivity Analysis rates. The results of the analysis of the Taman Melati Dinoyo Apartment project, Malang City, are that it has an NJOP value of Rp. 418,462,5800,000,- and was declared financially feasible with a positive NPV value of Rp. 55,585,691,096,- IRR is worth – 8.99% which is less than MARR, namely 7.79%, BCR <1, namely 0.7997 and the payback period is IDR, 186,959,656,- in year 2, sensitivity analysis shows the project an apartment is declared feasible if the increase in investment reaches 38% and the decrease in income is 20%.